Consent of E-Wallet Personal Data Subjects on Cross-Border Data Transfer - Dewi, Kadek Ary Purnama; Dharmawan, Ni Ketut Supasti (UNISSULA, 2024)
Indonesia is the highest country in Southeast Asia using electronic wallets or e-wallets. However, e-wallets as mobile payment services provide risks and problems for their users. The submission of personal data by users and the acceptance of personal data by e-wallet application providers are seen as legally enforceable statements of will. Protection of personal data on e-wallets is very necessary. The purpose of this research is to find out the protection of personal data which is the protection of human rights and the enforcement of the values of justice for consumers. This research is normative juridical research using analytical and conceptual approach, the statute approach and comparative approach. Literature study was conducted on the collection of primary and secondary legal materials, then the analysis was carried out qualitatively. The results of the research show that the regulatory model for the protection of personal data on e-wallets in the future requires arrangements regarding the obligation of consent from personal data subjects in personal data transfer activities both at home and abroad. Technical arrangements regarding the protection of personal data on e-wallets must be outlined in Bank Indonesia Regulations and Financial Services Authority Regulations.